Student Mobility or Emigration Flow? The Case of Students Commuting from Serbia to Hungary - Zoltan Takac; Éva Szügyi (DETUROPE)
Student mobility between two European countries in transition, Hungary and Serbia, was considered for the period 2001-2010. The high motivation and number of Hungarian-speaking students emigrating/commuting to Hungary began in 1990, with the beginning of the Yugoslav Wars. In 2010, 1,385 Hungarian-speaking students (from Vojvodina, Serbia) studied in Hungary and 3,152 in Serbia. Student mobility between Hungary and Serbia is highly concentrated and causes a very low returning rate of educated young elite (approximately 30%). For this reason, the future of the Hungarian minority has begun to be put into question in Serbia, in the Autonomous Province of Vojvodina, where their percentage within whole population is noticeably decreasing (1991: 16.9%, 2001: 14.3%). The research has been focused on answering the following questions: Are there integration conflicts in the autochthon minority within the state borders of Serbia? What can higher education offer to these students? Does the region offer enough to provide perspectives for young members of the elite? Will early student mobility end with continuous emigration? Empirical background: Interviews with young adult migrants from Serbia to Hungary; Location: Serbia. Objective: To examine the motives and willingness to emigrate among the Hungarian young adults/students from Vojvodina. Interview subjects: 18 university/college students or young adults with a diploma (from Vojvodina). It is important to note that only those young adults were interviewed who have returned to Serbia having finished their educational career or who are likely to come back later. Conclusions in brief: The Yugoslav Wars, worsening economic conditions, and low living standards have significantly influenced the willingness of the youth to migrate. The motives of migration among the Hungarian youth in Vojvodina are gaining professional experience, broadening knowledge, and improving language. Hungary is the first target country of migration for linguistic and cultural reasons and in the last 20 years has naturally become the target country of permanent settling and emigration of the young Hungarian elite.